Do methodological differences account for the current controversy on tissue factor expression in platelets?. (19th May 2018) - Brambilla, Marta; Rossetti, Laura; Zara, Chiara; Canzano, Paola; Giesen, Peter L.A.; Tremoli, Elena; Camera, Marina
Abstract: Tissue factor (TF), the key activator of the blood coagulation cascade and of thrombus formation, is also expressed by circulating human platelets. Despite the documented in-depth characterization of platelet TF carried out in the past 15 years, some authors still fail to identify TF in platelets, especially when assessment in platelet-rich plasma (PRP) or washed platelets is carried out. This study aims to extend the characterization of the subset of TF-positive platelets in PRP from healthy subjects and to verify how different centrifugation forces, used to prepare the PRP, could affect the analysis of TF-positive platelets. Data indicate that large-size platelets express significantly higher amount of TF compared to small-size cells, in terms of both TF protein and TF mRNA. Upon stimulation, large platelets readily expose on the cell membrane TF, which is functionally active, i.e., able to generate factor Xa (FXa) as well as thrombin. By contrast, TF activity in small platelets is almost completely quenched by tissue factor pathway inhibitor (TFPI), becoming indeed detectable only after treatment with an anti-TFPI antibody. Our data highlight that particular attention must be paid to the preparation and collection of the PRP since such preanalytical variables may influence the platelet recovery and in turn affect subsequent analysis, whether it is flow cytometry, functional activity tests, proteome, or transcriptome analysis. Indeed, the TF-positive subset of large platelets can easily be lost if centrifugation protocols are not optimized, thus erroneously leading to a false-negative result.